(untitled) (Revista Argentina de Musicología, 2022)
This paper studies the record productions of the Venezuelan band Zapato 3, at the time, one of the most important national rock groups. The methodology is qualitative and part of critical listening for the analysis of the mix based on the six criteria established by Owsinski (2017): balance, frequency, panorama, dimension, dynamics and interest; as well as a panoramic analysis of the disc based on the criteria of acoustic environment, transparency, musical balance, stereo image and sound color. According to the above, aspects of musical production, recording techniques and transmission of musical energy have been inferred. The corpus is made up of five record productions between 1989 and 1999, ten years marked by the change from analog to digital technology whose transition is defined by Luthar (2021) as “hybrid listening”. As a result, the modification of the audio was due to technical and creative possibilities that converged in the use of post-production techniques, such as the use of filters, compression, electronic processors, among others. The audio analysis was complemented with a documentary and bibliographic review of the band and was complemented with participant interviews: one with Eugenio Miranda, producer of the group’s first album, and José Antonio Cepeda, music producer.